LAND PROCUREMENT IN ORDER TO SUPPORT THE DEVELOPMENT REVIEWED FROM THE ASPECTS OF LEGAL CERTAINTY - Yunadi, Teddy (Ridwan Institute, 2024)
Article 5 of the Basic Agrarian Law of Indonesia establishes that the earth, water, space, and their natural resources are under the control of the state, with the aim of achieving public prosperity in a just society. In developing the electricity system, as per Law No. 30 of 2009 on Electricity, land use necessitates compensation for land rights holders in accordance with Law No. 2 of 2012 on Land Acquisition for Public Interest and related regulations. Regulation of the Minister of Energy and Mineral Resources No. 13 of 2023 addresses spatial planning, minimum distance for electric transmission networks, and compensation for land and buildings under these networks. However, land beneath the Extra High Voltage Overhead Line (SUTET) only receives compensation for land value, not for the use of the space beneath the line, leading to reduced land productivity and economic value. This research employs normative juridical research with statutory and case approaches, analyzing primary legal materials such as relevant laws and regulations. It utilizes legal theories including legal certainty, justice, and state welfare. The research finds that the current practice of not compensating land under SUTET, but only compensating for land value, results in economic disadvantage and lacks fairness. To promote legal certainty and justice, it is recommended that compensation provisions be explicitly regulated by law to address these issues comprehensively.